Enhancing library and information science education through cross-border collaboration: the experience of University of Ibadan, Nigeria and University of Ghana (2014)
Collaboration has been widely acknowledged as a potent tool for meeting the challenges of library and information science (LIS) education. Collaboration is forged not only among LIS institutions within national boundaries but also across borders. While collaboration is known to have been well developed in the developed countries of Europe and North America and is, indeed, advancing the cause of LIS education, not much seems to have been done in developing countries, particularly those in the West African region. Nigeria and Ghana are two West African countries with strong historical ties. They share, among others, a common colonial experience which culminated in the establishment of the University of Ibadan, Nigeria and the University of Ghana in the same year (1948) as affiliate colleges of University of London. The University of Ibadan’s Department of Library, Archival and Information Studies and the University of Ghana’s Department of Information Studies are notable centres of LIS education in West Africa. While the Ibadan LIS department started as the Institute of Librarianship in 1959 and admitted its first batch of six students in 1960, the Ghana LIS department evolved from the Ghana Library School established in 1961 under the auspices of Ghana Library Board. The two LIS departments have since been in the forefront in the development and sustenance of LIS education in West Africa. In view of their unique position and the long-standing relationship, what is the level of collaboration between them? This is what this study investigated. A survey research design was adopted with questionnaire and semi-structured interview with faculty in the two LIS institutions as instruments for data collection. Based on the findings and in the light of experiences in other parts of the world, recommendations are made towards improving collaboration in US education in the region.